2009
DOI: 10.1093/carcin/bgp286
|View full text |Cite
|
Sign up to set email alerts
|

Protein carbonyl levels, glutathione S-transferase polymorphisms and risk of colorectal cancer

Abstract: Oxidative stress has been associated with the carcinogenesis of colorectal cancer. Glutathione S-transferases (GSTs) modulate the elimination of free radical. We conducted a case-control study to examine the interaction between oxidative stress and GSTs polymorphisms on colorectal cancer risk. This study recruited 727 pathologically confirmed colorectal adenocarcinoma cases and 736 sex- and age-matched controls. Plasma protein carbonyls, as a parameter of oxidative stress, were measured using enzyme-linked imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 45 publications
0
23
0
2
Order By: Relevance
“…Because proteins have many different and unique biological functions, oxidative modifications of the proteins can lead to diverse functional consequences. Their enzymatic and binding activities may be inhibited, their susceptibility to aggregation and proteolysis may be increased, and their uptake by the cells may be increased or decreased in addition to their altered immunogenicity [3,6,7,14]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because proteins have many different and unique biological functions, oxidative modifications of the proteins can lead to diverse functional consequences. Their enzymatic and binding activities may be inhibited, their susceptibility to aggregation and proteolysis may be increased, and their uptake by the cells may be increased or decreased in addition to their altered immunogenicity [3,6,7,14]. …”
Section: Discussionmentioning
confidence: 99%
“…Carbonyl groups are introduced into proteins by various oxidative pathways. ROS can react directly with the proteins, or they can react with molecules such as sugars and lipids, generating products (reactive carbonyl species) that may react with proteins and lead to the formation of protein carbonyl derivatives [2,3,4,5,6,7]. …”
Section: Introductionmentioning
confidence: 99%
“…In the GSTP1 gene, several polymorphisms have been identified, including a non-synonymous-coding polymorphism resulting in a isoleucine to valine amino acid change at codon 105 (Ile105Val) and an alanine to valine amino acid change at codon 114 (Ala114Val) [57]. While one study showed levels of 8-oxo-7,8-dihydro-2′-deoxyguanosine to differ by GSTP1 but not GSTM1 or GSTT1 genotypes [58], another found no differences in protein carbonyl levels by any GST genotype [59]. …”
Section: Glutathione S-transferasesmentioning
confidence: 99%
“…According to the exclusion criteria, 13 publications were excluded including nine articles containing overlapping data [20][21][22][23][24][25][26][27][28], two about colorectal adenoma [29,30], one for being case-only study [31], and one for not about GSTT1 or GSTM1 polymorphism [32]. At last, data were available from 19 individual casecontrol studies [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] (a total of 3,130 CRC cases and 6,423 controls). Seventeen studies on GSTM1 polymorphism (a total of 2,987 CRC cases and 6,240 controls), 12 studies on GSTT1 polymorphism (a total of 2,509 CRC cases and 5,744 controls), and seven studies on GSTM1-GSTT1 interaction analysis (a total of 1,214 CRC cases and 4,189controls) were included in the meta-analysis.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…These 19 individual case-control studies were published from 1996 to 2010 with six in English [33,34,41,45,50,51] and 13 in Chinese [35-40, 42-44, 46-49]. Table 1 presents a brief description of these 19 case-control studies.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%